REINTERPRETATION OF LIVELIHOODS IN MARRIAGE LAW AND ITS IMPLICATIONS ON FAMILY RESISTANCE IN THE TIME AND POST COVID-19 - Mu'in, Fathul; Mukri, Moh.; Khairuddin, K.; Mahmudah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2021)
The rules regarding a living in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law imposes the obligation to earn a living only on the husband. These two regulations create problems in society. Many wives demand a living from their husbands. Not a few wives also have jobs and income, but they are spent on their own needs, including for consumptive things, channeling hobbies and others because they think that fulfilling a living is not part of their obligations. This condition is coupled with the interpretation of a number of verses of the Qur'an and the traditions of the Prophet which are still patriarchal. The marriage law and a number of verses of the Qur'an and the Prophet's hadith need to be reinterpreted. This is because the development of an increasingly advanced era makes the role of women not only as wives who only take care of the household, but also as one of the contributors to the economy. This research uses the library research method. This study concludes that the livelihoods in these two laws and regulations need to be updated to be relevant to current conditions. Supposedly, the wife also has the same obligation in matters of livelihood. The reinterpretation of livelihood using the interpretation of mubadalah is to produce the principle of mutuality. The wife can even be the main breadwinner under certain conditions. This interpretation has implications for the fulfillment of the family's economy during the pandemic and post-covid-19 pandemic. Because, in difficult economic conditions, the wife participates in helping the family economy on a macro basis or even as the main provider in the household who changes places with her husband.Keywords: Reinterpretation, Livelihoods, Marriage Law, Family Resistance, Covid-19